(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
On the day, the author displayed a photograph of the gold filagree watch that may have belonged to Bonnie Prince Charlie. This article gives some information about the watch’s provenance, as well as the life and works of the woman who owned it.